Evaluation of the MTBDRsl test for detection of second-line-drug resistance in Mycobacterium tuberculosis. - Kiet, V; Lan, N; An, D; Dung, N; Hoa, D; van Vinh Chau, N; Chinh, N; Farrar, J; Caws, M (2010)
The MTBDRsl assay (Hain Lifescience GmbH, Germany) is a new line probe assay for the detection of extensively drug-resistant tuberculosis (XDR TB). The test simultaneously detects resistance to ethambutol, aminoglycosides/cyclic peptides, and fluoroquinolones through detection of mutations in the relevant genes. The assay format is identical to the MTBDR Hain assay. The assay was evaluated for the detection of second-line-drug resistance in Vietnamese isolates using two sample sets from the microbiology department of Pham Ngoc Thach Hospital, Ho Chi Minh City, Viet Nam, with existing conventional phenotypic drug susceptibility results for second-line drugs: 41 consecutive fluoroquinolone-resistant isolates and 21 consecutive multidrug-resistant but fluoroquinolone-sensitive isolates. The sensitivity for detection of fluoroquinolone resistance was 75.6% (31/41) (95% confidence interval [95% CI], 59.7% to 87.6%), and for kanamycin resistance, the sensitivity was 100% (5/5) (95% CI, 47.8% to 100%). The sensitivity of the test for detection of ethambutol resistance was low, consistent with previous reports, at 64.2% (34/53) (95% CI, 49.8% to 76.9%). The specificity of the test was 100% for all three drugs. These data suggest that the MTBDRsl assay is a rapid, specific test for the detection of XDR TB but should not be used exclusively to "rule out" second-line-drug resistance. Further operational evaluation is required and should be integrated with evaluations of the MTBDR test.